Oat - a multifunctional grain - Peterson, David M. (MTT, 2004)
The multifunctional uses of oat include animal feed, human food and raw material for food, health care, and cosmetic products. The major components of oat that contribute to its functions include protein, oil, starch and â-glucan. In addition, there are minor components, including tocols and avenanthramides, that have antioxidant properties and may contribute to human health and well being.
Keywords: Ka; food; feed; protein; oil; â-glucan; avenanthramides; tocols